Systematic Deletion of the Adenovirus-associated RNA(I) Terminal Stem Reveals a Surprisingly Active RNA Inhibitor of Double-stranded RNA-activated Protein Kinase - Wahid, Ahmed M. (American Society for Biochemistry and Molecular Biology, 2008)
Adenoviruses use the short noncoding RNA transcript virus-associated (VA) RNA(I) to counteract two critical elements of the host cell defense system, innate cellular immunity and RNA interference, mediated by the double-stranded RNA-activated protein kinase (PKR) and Dicer/RNA-induced silencing complex, respectively. We progressively shortened the VA RNA(I) terminal stem to examine its necessity for inhibition of PKR. Each deletion, up to 15 bp into the terminal stem, resulted in a cumulative decrease in PKR inhibitory activity. Remarkably, however, despite significant apparent destabilization of the RNA structure, the final RNA mutant that lacked the entire terminal stem (TSΔ21 RNA) efficiently bound PKR and exhibited wild-type inhibitory activity. TSΔ21 RNA stability was strongly influenced by solution pH, indicating the involvement of a protonated base within the VA RNA(I) central domain tertiary structure. Gel filtration chromatography and isothermal titration calorimetry analysis indicated that wild-type VA RNA(I) and TSΔ21 RNA form similar 1:1 complexes with PKR but that the latter lacks secondary binding site(s) that might be provided by the terminal stem. Although TSΔ21 RNA bound PKR with wild-type K(d), and overall change in free energy (ΔG), the thermodynamics of binding (ΔH and ΔS) were significantly altered. These results demonstrate that the VA RNA(I) terminal stem is entirely dispensable for inhibition of PKR. Potentially, VA RNA(I) is therefore a truly bi-functional RNA; Dicer processing of the VA RNA(I) terminal stem saturates the RNA interference system while generating a “mini-VA RNA(I)” molecule that remains fully active against PKR.